The History, Law and Practice of Cabinet Immunity in Canada - Campagnolo, Yan (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 2017)
Canada has the dubious honour of being the sole Westminster jurisdiction to have enacted a near-absolute immunity for Cabinet confidences. Through the adoption of sections 39 of the Canada Evidence Act and 69 of the Access to Information Act in 1982, the federal Parliament has deprived the courts of the power to inspect Cabinet confidences and order their disclosure when the public interest demands it. Why has Parliament enacted these draconian statutory provisions? How have these provisions been interpreted and applied since they have been proclaimed into force? This article seeks to answer these questions based on a detailed examination of the relevant historical records, parliamentary debates, case law and government reports. The first section seeks to demonstrate that the political decision to provide a near-absolute immunity for Cabinet confidences was made at the highest level of the State, by Prime Minister Pierre Elliott Trudeau, based on the debatable justification that the courts could not be trusted to properly adjudicate Cabinet immunity claims. The second section seeks to establish that the government has taken advantage of the inherent vagueness of sections 39 and 69 to give an overbroad interpretation to the term “Cabinet confidences.” In addition, by modifying the Cabinet Paper System, the government has significantly narrowed the scope of an important exception to Cabinet immunity, that is, the “discussion paper exception,” which was initially intended to provide some level of transparency to the Cabinet decision-making process. These problems are compounded by the fact that only a weak form of judicial review is available against Cabinet immunity claims which, in practice, makes it tremendously difficult to challenge such claims.